A1.18 Mesenchymal stem cells lose their immuno-protective effects upon changes in their local microenvironment. (24th February 2016) - Munir, H; Benjamin, A; Allwood, JW; Dunn, WB; He, S; Nash, GB; McGettrick, HM
Abstract : Background and objectives: Mesenchymal stem cells (MSC) act as endogenous regulators of the inflammatory infiltrate, communicating with blood vascular endothelial cells (EC) to limit leukocyte recruitment. Indeed exploiting these properties therapeutically is the principle underpinning clinical trials into chronic inflammatory diseases, including rheumatoid arthritis (RA). However, chronic inflammation is associated changes in the phenotype or function of MSC and their progeny, including ectopic fat deposits, which might represent damage-induced aberrant MSC differentiation. Here we examine how adipogenic differentiation of MSC influenced EC recruitment of leukocytes. Methods: Co-cultures of EC with either MSC or MSC-derived adipocytes were formed on either side of porous filters and stimulated with tumour necrosis factor α (TNFα) for 4h. Neutrophil adhesion from flow was assessed by phase contrast microscopy. Microarray analysis was performed on EC and MSC following co-culture and assessed using BIOGRID and REACTOME. Metabolomic analysis was performed using mass spectrometry and analysed using PUTMEDID-LCMS workflows operating in the Taverna workflow environment. Results: MSC were immunosuppressive, inhibiting neutrophil recruitment to TNFα-treated EC. Conditioned media from MSC-EC co-cultures, but not MSC mono-cultures, was able to recapitulate these effects and IL-6 was identified as the bioactive mediator. In co-culture, EC up-regulated 464 genes linked cytokine (eg, IL-6, IL-1) and chemokine (e.g. CXCL2) signalling pathways and leukocyte-endothelial interactions (eg, E-selectin). Moreover, 49 metabolites were up-regulated in EC following co-culture with MSC, including arachidonic acid metabolism, tryptophan and tyrosine metabolism, branched chain amino acids and sphingolipid metabolism. In contrast, MSC-derived adipocytes were no longer able to suppress PMN adhesion to inflamed EC. Neutralisation of IL-6 reversed the stimulatory effects of MSC-derived adipocytes in co-culture. Here we identified >40 extracellular metabolites differentially expressed between the EC-MSC and EC-MSC-derived adipocyte co-cultures. Conclusions: Thus in the correct environment MSC act to endogenously dampen EC responses to cytokines, thereby limiting leukocyte recruitment in an IL-6 dependent manner. However, upon differentiation MSC lose this intrinsic immuno-protective capacity, adopting a more stimulatory, pro-inflammatory behaviour. Alterations in the phenotype and function of MSC may contribute to pathogenic inflammatory responses by altering the way in which IL-6 exerts its effects from anti-inflammatory to pro-inflammatory.